2013
DOI: 10.1002/dys.1450
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐assisted Interventions Targeting Reading Skills of Children with Reading Disabilities – A Longitudinal Study

Abstract: The purpose of the present study was to examine the effects of three computerized interventions on the reading skills of children with reading disabilities in Grade 2. This longitudinal intervention study included five test sessions over 1 year. Two test points occur before the intervention, and three afterwards. The last follow-up was conducted 1 year after the first measurement. One hundred thirty children in Grade 2 participated in the study. Three groups of children with reading difficulties received compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 47 publications
(61 reference statements)
4
46
0
8
Order By: Relevance
“…Although the study of mobile-supported reading interventions is still in its infancy, several studies have found positive effects of computerized reading intervention programs for the teaching of initial reading skills with students at risk for reading failure (Fälth et al 2013;Grindle et al 2013;Volpe et al 2011). For example, a computerized tutoring program was used to teach letter sounds to four kindergarten students at risk for reading failure, two of which were ELLs (Volpe et al 2011).…”
Section: Effects Of Educational Technology On Reading and Engagement mentioning
confidence: 99%
“…Although the study of mobile-supported reading interventions is still in its infancy, several studies have found positive effects of computerized reading intervention programs for the teaching of initial reading skills with students at risk for reading failure (Fälth et al 2013;Grindle et al 2013;Volpe et al 2011). For example, a computerized tutoring program was used to teach letter sounds to four kindergarten students at risk for reading failure, two of which were ELLs (Volpe et al 2011).…”
Section: Effects Of Educational Technology On Reading and Engagement mentioning
confidence: 99%
“…We would also argue that it is necessary to examine how cognitive aspects of learning to read and write, such as background experiences and metalinguistic awareness, interact with screen-based practices and socio-cultural settings. Knowledge gained from cognitive neuroscience suggests that mental abilities or executive skills related to working memory and attention are essential to reading comprehension and writing development (García-Madruga et al, 2013) and can be explicitly taught and supported by digital technologies and virtual environments (Fälth et al, 2013). Central questions in this context are: What happens to early literacy development when reading and writing instruction goes online, and how are pupils' text awareness and reflective learning influenced?…”
mentioning
confidence: 99%
“…This learning environment supports the child's access to long-term representations, shortterm maintenance and manipulation, sustained attention and engagement in working with the material, and is thus likely to facilitate learning (Mayer, 2008). In fact, Omega-is and its predecessors were developed with difficult learning situations in mind, and the program and its forerunners have shown positive effects on both word reading and reading comprehension in typically developing as well as children with, e.g., dyslexia, autism, and attention deficit hyperactivity disorder (e.g., Fälth, Gustafson, Tjus, Heimann, & Svensson, 2013;Gustafson, Fälth, Svensson, Tjus, & Heimann, 2011;Heimann, Nelson, Gillberg, & Karnevik, 1993;Heimann, Nelson, Tjus, & Gillberg, 1995;Helland, Tjus, Hovden, Ofte, & Heimann, 2011;Tjus, Heimann, & Nelson, 1998. Early versions of the program also indicated positive effects on reading development in deaf children (Prinz, Nelson, & Stedt, 1982;Prinz & Nelson, 1985).…”
Section: Using Interventions To Support Reading Developmentmentioning
confidence: 99%